Federalism matters: evaluating the impact of sub-federal governments in Canadian and American foreign trade policy - Kukucha, Christopher J. (Canadian foreign policy journal, 2015)
This study will argue that federalism in Canada and the United States, especially its institutional form and practice, directly impacts the influence of sub-federal governments in the negotiation and implementation of international trade agreements. In highlighting the durability of domestic federal institutions, it challenges "decline of the state" arguments often found in the international relations and global political economy literature. It also expands traditional studies of federalism beyond questions of centralization/decentralization and the impact of globalization on federal systems. Case studies include the Canada-United States "Buy American" Procurement Agreement, the Canada - European Union Comprehensive Economic and Trade Agreement (CETA) and several international trade disputes involving American states.